THE IMPACT OF EU’S NEW PACT ON MIGRATION DIPLOMACY - Nur Seda Temur (Uluslararası İlişkiler Çalışmaları Dergisi)
As the European Union launched its New Pact on Migration and Asylum on 23 September 2020, many anticipated certain changes in foreign policies of EU member states. Within this context, migration diplomacy was not the exception. Regarding this inference, this article will examine the following question: How will the EU’s New Pact on Migration and Asylum impact migration diplomacy? Concerning this question, in this article, I will try to defend the idea that although the New Pact strengthens the interdependency between EU member states, immigration towards EU member states will be complicated, which will raise the importance of migration diplomacy among migration-receiving, migration-sending, or transit states. With respect to this claim, after the introduction part, this research paper will first focus on the concept of migration diplomacy, and the discussion of the term from realist theoretical framework. After this, the EU’s New Pact on Migration and Asylum will be examined, and its comparison with the 2008 EU’s Pact on Migration and Asylum will be made. Before the concluding remark, the impact of the New Pact on migration diplomacy will be discussed. In the conclusion part, an overall evaluation will be made. This research paper will be a qualitative study. In particular, the data about decision taken in the New Pact on Migration and Asylum will be gathered from both primary and secondary resources through document analysis.